Between decentralization and deconcentration of environmental management: reaches and limits in the perfomance of municipal environmental councils in the Northeastern Semi-arid region - Aguiar, Wagner José de; Braga, Ricardo Augusto Pessoa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2018)
The Brazilian Federal Constitution of 1988 had an important role in the induction of political-administrative decentralization as in the elevation of municipalities as a federated entity. In environmental policy, these results have been expressed through the dissemination of municipal environmental councils. In the Northeast of Brazil, a region that has the fewest municipalities with established environmental councils and researches focused on their dynamics, new collegiate instances have been created, without a critical evaluation, among other factors, of the institutional capacity of small municipalities. In this sense, this article discusses the reaches and the limits identificated in the perfomance of municipal councils of environment in the Northeastern Semiarid, taking as an analytical reference the logics of the decentralization and the desconcentration. Through a bibliographical survey and a case study carried out in the semi-arid municipalities of Pernambuco, it is possible to identify reaches but, above all, limits that hinder the deliberative autonomy of the councils, even in large and economically dynamic municipalities. New studies are suggested, considering the pioneering and new environmental councils, especially in the northeastern states that exhibit the lowest levels of environmental management instruments implemented.